Análise in silico e caracterização bioquímica parcial de uma Beta-glicosidase da cianobactéria amazônica Microcystis aeruginosa Caciam 03 - SERRA, Gustavo Marques (2022)
The β-glucosidases (EC 3.2.1.21) are a diverse group of enzymes that catalyze the hydrolysis of β-glycosidic bonds of carbohydrate to release non-reducing glycosyl residues, such as β-Dglucose and have wide industrial applicability. In bacteria organisms, the β-glucosidase that constitute the microbial cellulase complex play an important role in the regulation of the entire process of cellulose hydrolysis. Cyanobacterial β-glucosidases are believed to play roles in glycoside metabolism, carbohydrate cycling and possible hydrolytic activity of shortchain oligosaccharides and cellobiose important for complete cellulose hydrolysis. However, structural and functional data on cyanobacterial β-glycosidases and their biotechnological application are still scarce. In this context, the present work seeks to elucidate the physicochemical, structural and functional properties using in silico tools and to present the biochemical characterization of a β-glycosidase from Microcystis aeruginosa CACIAM 03 (MaBgl3). The sequence used in this study was deposited at the NCBI (ID: 13127.1), it had been analyzed in terms of its physicochemical properties, primary sequences, functions, subcellular location, domains, secondary structures and three-dimensional structures. This β- glycosidase MaBgl3 belongs to the GH3 family, it’s monomeric and has a theoretical molecular mass of 57,24 kDa and pI of 5.01, configuring it to be and acidic protein present in the cytoplasm of cyanobacteria. The modeled structure of MaBgl3 revealed an N-terminal domain folded like a distorted TIM barrel (β/α)8 with similar dyad catalytic mechanics found in N-acetylglucosaminidases, a loop connecting that domain to a second C-terminal domain folded in α/β-sandwich. The enzymatic extract showed activity against p-nitrophenyl-β-Dglucopyranoside, having optimum activity at pH 4.5 and 40 °C with activity of 37 U/mL. These results allowed us to understand the main biochemical, structural characteristics and their catalytic mechanism. In the future, assessments of glucose tolerance, influence of additives and enzyme purification, may contribute to lignocellulosic biomass hydrolysis processes, among other biotechnological applications.